"Biomass production and yield in irrigated maize at different rates of nitrogen in a semi-arid climate". (1st December 2020) - López Córcoles, H.; de Juan, J.A.; Picornell, M.R.
Highlights: Within intensively cultivated and irrigated areas, local experimentation becomes essential to improve N use efficiency. This allows modelling the response that crops, such as maize, have to different N fertilizer rates. A fertilizer rate in the range of 150–200 kg N ha −1 should be adopted by the farmers. This will reduce N fertilizer cost by 33–55 % and will reduce the risk of nitrate leaching. Regional Technology transference centres are incorporating these studies results in a Support System Decision. Abstract: Nitrogen fertilization has a significant environmental impact in Europe due to the problems of wide-spread pollution. This paper deals with a series of field experiments conducted in a semiarid region of Southeast Spain. Irrigated maize was grown under different N fertilizer rates: control as in no nitrogen applied (C; 0 kg N ha ―1 ); conventional amount of nitrogen (Nc; 300 kg N ha ―1 ); and theoretical optimum (No; 130 kg N ha ―1 ) in a randomised block design with three replications. In 1999 and 2000, when 175 and 150 kg N ha ―1 were respectively applied to No treatment, no significant differences were found. With the Nc treatment, a grain yield of 17.6 Mg ha ―1 was obtained in 2001, being significantly higher than the yield obtained with the No treatment (15.8 Mg ha ―1 ). This means that No rate was under the technical optimum, but both treatments were higher than C treatment (7.2 Mg ha ―1 ). A fertilizer rate of 130 kg N ha ―1 was lower than necessary to obtain maximum yields, although the rate of 150 kg N ha ―1 did not show significant differences with regard to Nc treatment (300 kg ha ―1 ) (2000). Studies about crop response to different N rates could be very useful for farmers. Regional Technology Transfer Centres are incorporating the results of these studies in a Decision Support System (DSS).